Five e-learning courses (FAO e-learning academy) on mechanization business models - CGIAR Research Program on Maize (2021)
e-learning courses are available in English and Spanish on FAO e-academy website. Courses in Spanish will be available by 1st quarter 2022. https://elearning.fao.org/course/view.php?id=711 https://elearning.fao.org/course/view.php?id=712 https://elearning.fao.org/course/view.php?id=780 https://elearning.fao.org/course/view.php?id=780 https://elearning.fao.org/course/view.php?id=713